On some generalized recent operators in topological Spaces - Siham I. Aziz; Nabila I. Aziz (Tikrit Journal of Pure Science)
In this paper we introduce a new classes of operators namely (regular generalized*, regular generalized**, generalized **regular) (briefly, rg*, rg **, g**r, respectively) in topological spaces and study some of their properties with some important theorems.